2021
DOI: 10.3390/ijms22031421
|View full text |Cite
|
Sign up to set email alerts
|

Loganin Attenuates the Severity of Acute Kidney Injury Induced by Cisplatin through the Inhibition of ERK Activation in Mice

Abstract: Cisplatin is the most widely used chemotherapeutic agent. However, it often causes nephrotoxicity, which results in acute kidney injury (AKI). Therefore, we urgently need a drug that can reduce the nephrotoxicity induced by cisplatin. Loganin is a major iridoid glycoside isolated from Corni fructus that has been used as an anti-inflammatory agent in various pathological models. However, the renal protective activity of loganin remains unclear. In this study, to examine the protective effect of loganin on cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…As early as 30 years ago, researchers proposed that cisplatininduced free iron overload leads to lipid peroxidation in kidneys, but the link between ferroptosis and Cis-AKI has only recently been recognized. Denget al [5] confirmed that cisplatin induced free iron release, GSH depletion, a decrease in GPx4 activity and excessive lipid peroxidation in vivo and in vitro, which was subsequently verified by other groups of investigators [2][3][4]. Ferroptosis, officially named in 2012, is characterized by intracellular iron accumulation and lipid peroxidation apart from classical apoptosis, necrosis, and autophagy [44].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As early as 30 years ago, researchers proposed that cisplatininduced free iron overload leads to lipid peroxidation in kidneys, but the link between ferroptosis and Cis-AKI has only recently been recognized. Denget al [5] confirmed that cisplatin induced free iron release, GSH depletion, a decrease in GPx4 activity and excessive lipid peroxidation in vivo and in vitro, which was subsequently verified by other groups of investigators [2][3][4]. Ferroptosis, officially named in 2012, is characterized by intracellular iron accumulation and lipid peroxidation apart from classical apoptosis, necrosis, and autophagy [44].…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have shown that DNA damage, oxidative stress, inflammation, vascular dysfunction, and mitochondrial damage may be involved in the pathogenesis of Cis-AKI [1]. Recently, several studies [2][3][4][5][6] have suggested that cisplatin treatment leads to excessive lipid peroxidation, ferritinophagy-mediated free iron release, and a decrease in the activity of glutathione peroxidase-4 (GPx4), indicating the close link between ferroptosis and Cis-AKI. Hence, ferroptosis intervention may be an effective strategy to attenuate Cis-AKI; nevertheless, there have not been specific drugs against ferroptosis in clinical application to date.…”
Section: Introductionmentioning
confidence: 99%
“…In our results, the GSH-based antioxidant system of the liver was comprehensively elevated after the intervention of C-phycocyanin. Cisplatin treatment (10 mg/mL same dose as us) has been found to cause Ferroptosis ( 32 ), and cisplatin-induced depletion of GSH and inactivation of GSH-Px play a central role in the mechanism of Ferroptosis ( 33 ). This means that different from the antioxidant effect on kidney, the antioxidant effect of C-phycocyanin on liver might be resisting Ferroptosis by the GSH pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Renal inflammation also plays an important role in cisplatin-induced AKI progression [ 36 , 37 , 38 ]. Thus, the levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) are elevated in cisplatin-induced AKI [ 39 , 40 , 41 ]. The elevation of pro-inflammatory cytokine levels is mediated by the activation of signaling cascade, MAPKs and NF-κB, which are associated with various cell functions, including proliferation, division, stress response, inflammation, and apoptosis [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%